Salmonella cross-contamination of pork for health risk assessment: Simulation of cooking preparation at households - Dang Xuan Sinh; Phuc Pham Duc; Nguyen Hai Nam; Nguyen Tien Thanh; Vu Thi Kim Hue; Nguyen Hung Long; Hung Nguyen-Viet (2014)
A survey on 153 households and four scenarios using Salmonella artificially inoculated and boiled pork processing was conducted to determine the rate and risk of cross-contamination on boiled pork. The results showed that 80% of households in Hung Yen eat boiled pork, 93% of them washed raw pork more than two times and boiled in 18.6 ± 8.6 minutes. Simulation experiments indicated that hands, washed water, knives and cutting boards (88.9-100%) exposed to raw contaminated pork were the main source of spreading to the other surfaces, stuffs and foods if not well controlled. Moreover, the experiment demonstrated a very high risk of contamination to boiled pork when using the same hands, knife and cutting board. Among simulation scenarios, using the same cutting board induced the highest risk of cross-contamination with Salmonella (66.7%), the same knife (11.1%) and the same hand (0%). These findings emphasize the role of cleaning hands properly, and processing tools as well as the separate set of knives and cutting boards for cooked food would significantly reduce cross-contamination of Salmonella.